Kejadian Depresi pada Pegawai Menjelang Pensiun, Studi pada Kepala Desa Di Lima Kecamatan, Kabupaten Demak - Rosanti, Tutik Ida; Krisnansari, Dyah (Jurnal Keperawatan Soedirman, 2010)
Pension is a psychisicial stressor. When stressor happened to a person he will hold an adjustment. If these efforts do not successful there will be problems such as this depression. The aim of this research is to determine the relationship between the retirement of employees with depression approaching retirement. The study was an observational analytic, a cross sectional approach. This study was conducted in November 2008 in Demak regency. The total population is 100 people, and samples 80 people. Variable measured amount is retired and measuring depression. TheTool used in this study are the data term mayor and HDRS (Hamilton depression rating scale). Chi square test result give p value = 0.02 (p less than 0.05), meaning that there is significant correlation between retirement with depression. Odds ratio was 2.25 (95% CI, 1.07